INTERVENSI POSTER “POKEZI” DAN EFEKTIVITASNYA PADA PENGETAHUAN, SIKAP, DAN PERILAKU KONSUMSI PANGAN BERISIKO PADA SISWA KELAS X SMK PPN BANJARBARU - Pitaloka, Anis Diah; Andrestian, Meilla Dwi; Anwar, Rosihan (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackround: The Riskesdas team (2018) reported that the proportion of risky consumption habits in adolescents aged 15-19 years which were more than 1 time per day was sweet food 52.30%, sweet drinks 63.67%, and food containing flavorings 73.29 % consumed more than once a day. Banjarbaru State SMK-PP students have poor food consumption habits. Thus, it is necessary to develop the poster media